2006
DOI: 10.1128/iai.74.3.1673-1682.2006
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Quenching by an N -Acyl-Homoserine Lactone Acylase from Pseudomonas aeruginosa PAO1

Abstract: The virulence of the opportunistic human pathogen Pseudomonas aeruginosa PAO1 is controlled by an N-acyl-homoserine lactone (AHL)-dependent quorum-sensing system. During functional analysis of putative acylase genes in the P. aeruginosa PAO1 genome, the PA2385 gene was found to encode an acylase that removes the fatty acid side chain from the homoserine lactone (HSL) nucleus of AHL-dependent quorum-sensing signal molecules. Analysis showed that the posttranslational processing of the acylase and the hydrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
254
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(271 citation statements)
references
References 60 publications
17
254
0
Order By: Relevance
“…This is consistent with the observation in the present study, that a pvdQ mutant produces precursors with myristic or myristoleic acid still bound to the L-Glu residue. The physiological function of PvdQ is therefore not in the deacylation of the quorum sensing molecule 3-oxo-C12 as previously suggested [14] but in the deacylation of the PVDI precursor isolated in the present work.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is consistent with the observation in the present study, that a pvdQ mutant produces precursors with myristic or myristoleic acid still bound to the L-Glu residue. The physiological function of PvdQ is therefore not in the deacylation of the quorum sensing molecule 3-oxo-C12 as previously suggested [14] but in the deacylation of the PVDI precursor isolated in the present work.…”
Section: Discussionsupporting
confidence: 57%
“…This precursor has been purified and was proposed to be a substrate of PvdQ [8], providing a direct link between PvdQ and the mechanism of myristate group removal by PvdQ before Abbreviations: PVDI, pyoverdine I; PVDIq, PVDI precursor produced by PAO1pvdQ; NRPS, non-ribosomal peptide synthetases; CA, collision activation; HPLC-MS, high performance liquid chromatography-mass spectrometry secretion into the extracellular milieu. PvdQ belongs to the NTN hydrolase family [13] and was identified as a periplasmic quorum-quenching protein that cleaves acyl homoserine lactones [14]. Transport of newly synthesized PVDI from the periplasm into the extracellular medium involves PvdRT-OpmQ, an ATP-dependent efflux pump [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, homologues of AiiD were also found in various other Ralstonia and Pseudomonas spp. (46), and these bacteria were later confirmed to also possess AHL acylase activity (42,44,45,47,51,52). Biochemical analysis of the fate of 3OC10HSL incubated with purified AiiD protein confirmed that AiiD functions as an AHL acylase, releasing HSL and 3-oxodecanoic acid as the major degradation products (46).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 88%
“…Other enzymes exhibited more flexibility in their requirements for substrate side chain structure. The substrate side chain of PGA can be an aromatic or aliphatic carboxyl group with 2-6 carbons (with k cat range from 4 to 15 s Ϫ1 , supplemental Table S1), whereas that of PvdQ can be 4 -14 carbons long (40). Because these enzymes lack the special residue, which controlled the cleavage site shift in CA, covalent binding of the spacer became more important for the second cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Specific Binding and Covalent Binding for the Second Cleavage-In the previous studies, besides CA, PGA and PvdQ were confirmed to be Ntn hydrolases that require two-step proteolysis for activation, releasing spacers consisting of 54, 22, or 23 aa, respectively (39,40) (Table 4). The long distances between the second cleavage sites and the Ntn Ser residues were also observed in the respective crystal structures (7,41).…”
Section: Discussionmentioning
confidence: 99%